Relation between emotions and education in science: state of the art reported in academic events (2021)
In science teaching, research around the affective domain is becoming increasingly important, given its influence on science teaching and learning. This article is an update of the doctoral research The relation between the emotions of teachers in service at the primary level and their professional development in the context of science education. It seeks to present the state of the art of the relation between emotions and science education from tertiary sources, which reflect the papers presented at highly relevant academic conferences. This review had a 19-year observation window—2000-2019—obtaining a total of 39 communications. The methodology used was based on the bibliographic mapping proposed by Molina et al. (2012) and the analysis of documents described by Quintana and Montgomery (2006). The methodology used started from the bibliographic informational mapping proposed by Molina et al., (2012), and the documentary analysis described by Quintana and Montgomery (2006). Since this review, important advances have been found and, similarly, it shows a still incipient research work on emotions and science education in settings such as elementary school and in-service teachers.